Ответ:
[tex]3. 1) x^{2} y-xy^2-y=y(x^{2} -xy-1)\\2) a^4-3a^3+4a^2=a^2(a^2-3a+4)\\3) 3a^3b-6a^3b^2+9a^4b=3a^3b(1-2b+3a)\\4. 1) 10b(a-c)-7(a-c)=(a-c)(10b-7)\\2) (a+b)+x(a+b)=(a+b)(1+x)\\3) (a-b)-11c(a-b)=(a-b)(1-11c)[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]3. 1) x^{2} y-xy^2-y=y(x^{2} -xy-1)\\2) a^4-3a^3+4a^2=a^2(a^2-3a+4)\\3) 3a^3b-6a^3b^2+9a^4b=3a^3b(1-2b+3a)\\4. 1) 10b(a-c)-7(a-c)=(a-c)(10b-7)\\2) (a+b)+x(a+b)=(a+b)(1+x)\\3) (a-b)-11c(a-b)=(a-b)(1-11c)[/tex]